2020
DOI: 10.4292/wjgpt.v11.i4.69
|View full text |Cite
|
Sign up to set email alerts
|

Role of telomere shortening in anticipation of inflammatory bowel disease

Abstract: BACKGROUND The existence of genetic anticipation has been long disputed in inflammatory bowel disease (IBD) in the absence of the explanatory mechanism. AIM To determine whether it was predictive of genetic anticipation, we evaluated telomere length in IBD. We hypothesized that multiplex IBD families exhibit a genetic defect impacting telomere maintenance mechanisms. METHODS We studied three IBD families with multiple affected members in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…Classically, telomere shortening has been linked with dysplasia and neoplasia in ulcerative colitis [ 74 , 75 ]. A study by Truta B et al found no clear link between telomere shortening in anticipation of IBD, although the authors stated that more studies are needed with larger sample sizes to confirm or refute their findings [ 75 ].…”
Section: Telomeres In the Context Of The Immune System And Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Classically, telomere shortening has been linked with dysplasia and neoplasia in ulcerative colitis [ 74 , 75 ]. A study by Truta B et al found no clear link between telomere shortening in anticipation of IBD, although the authors stated that more studies are needed with larger sample sizes to confirm or refute their findings [ 75 ].…”
Section: Telomeres In the Context Of The Immune System And Ibdmentioning
confidence: 99%
“…Classically, telomere shortening has been linked with dysplasia and neoplasia in ulcerative colitis [ 74 , 75 ]. A study by Truta B et al found no clear link between telomere shortening in anticipation of IBD, although the authors stated that more studies are needed with larger sample sizes to confirm or refute their findings [ 75 ]. Nevertheless, age-related telomere loss could contribute to immune dysfunction and the autoimmune response and could therefore explain the onset of IBD after middle age.…”
Section: Telomeres In the Context Of The Immune System And Ibdmentioning
confidence: 99%
“…Similarly, Isaevska et al ( 104 ) reported that for pregnant mothers, air pollution factors were related to shorter telomeres at birth, which can increase the long-term incidence of asthma and other diseases in children. In the study of Chakravarti et al ( 46 ) found that telomere dysfunction leads to activation of ATM/YAP1 pathway, which is related to the pathogenesis and severity of inflammatory bowel disease (IBD).However, some scholars also believe that no evidence has been found that TL is associated with IBD in children ( 47 , 48 ).…”
Section: Pediatric Diseases In Other Body Systemsmentioning
confidence: 99%
“…В связи с тенденцией к персонализации медицины и поиску геномных, протеомных и метаболомных предикторов внутренних болезней активно изучается корреляция длины теломер у пациентов с соматической патологией: нарушениями углеводного обмена [ 9 ][ 10 ], сердечно-сосудистыми заболеваниями [ 11 ], воспалительными заболеваниями желудочно-кишечного тракта [ 12 ], ожирением [13–15] и т.д.…”
unclassified